2008
DOI: 10.1177/1545968308324227
|View full text |Cite
|
Sign up to set email alerts
|

Increased Pinch Strength in Acute and Subacute Stroke Patients After Simultaneous Median and Ulnar Sensory Stimulation

Abstract: Peripheral sensory stimulation of the paretic hand may increase pinch strength of acute and subacute stroke patients immediately after stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(88 citation statements)
references
References 25 publications
0
86
1
1
Order By: Relevance
“…666,728,729,[731][732][733] A variety of interventions have been the focus of ≥1 studies but have not yet been shown to be consistently beneficial for upper limb motor rehabilitation. These include somatosensory stimulation [734][735][736][737][738] and noninvasive brain stimulation (transcranial magnetic stimulation or tDCS) in combination with upper extremity exercise therapy, [739][740][741][742][743][744][745][746] interventions targeting motor apraxia, 458 and manual therapy approaches such as stretching, passive exercise, and mobilization, 748 although these approaches are a routine part of practice for individuals with more severely affected upper extremities to prevent contractures and to manage spasticity.…”
Section: Iib Bmentioning
confidence: 99%
“…666,728,729,[731][732][733] A variety of interventions have been the focus of ≥1 studies but have not yet been shown to be consistently beneficial for upper limb motor rehabilitation. These include somatosensory stimulation [734][735][736][737][738] and noninvasive brain stimulation (transcranial magnetic stimulation or tDCS) in combination with upper extremity exercise therapy, [739][740][741][742][743][744][745][746] interventions targeting motor apraxia, 458 and manual therapy approaches such as stretching, passive exercise, and mobilization, 748 although these approaches are a routine part of practice for individuals with more severely affected upper extremities to prevent contractures and to manage spasticity.…”
Section: Iib Bmentioning
confidence: 99%
“…Previous studies have shown that a single 30 minute session of TENS can improve function immediately afterwards, 28,29 but the current results are the first to assess the effects of TENS during stimulation and while mobile. They suggest that the effects of TENS are almost immediate.…”
Section: Discussionmentioning
confidence: 88%
“…Low frequency stimulation protocols were not able to induce changes in this task. Single Pulse (0.66 Hz) muscle stimulation only improved the adaption of grip force to load force during the lift (by approximately 16 %), which was not correlated to the ARAT scores (McDonnell et al, 2007).Also TENS over the median and ulnar nerve did not affect ARAT scores regardless of whether the intensity was set to strong paresthesias or sensory threshold (Klaiput & Kitisomprayoonkul, 2009). In opposition to that, continuous sensory stimulation of the palm at 25 Hz for 15 minutes increased ARAT performance in those 6 out of 10 participants that had the lowest baseline performance (Sullivan & Hedman, 2007).…”
Section: Parameter Choice and Effectiveness Of Tactile Stimulation 48mentioning
confidence: 99%
“…Also low frequency TENS of the arm or the wrist extensors (20 Hz) at motor intensity had no influence (Powell et al, 1999;Sawaki, Wu, Kaelin-Lang, & Cohen, 2006). Only, if the site of stimulation was increased to the median and ulnar nerve, and the intensity was increased to induce strong paresthesia, this led to an increase in tip grip strength by 10.35 % and in lateral pinch strength by 9.6 % (Klaiput & Kitisomprayoonkul, 2009). Also stimulation at 40 Hz, eliciting maximal contraction influence both, grip strength (15 %) and pinch strength (35 %) in stroke patients (Thrasher, Zivanovic, McIlroy, & Popovic, 2008).…”
Section: Rts Induced Behavioral Effects On Motor Control and Possiblementioning
confidence: 99%
See 1 more Smart Citation